Performance of cattle stall-fed for beef in Malawi - Nkhonjera, L.P.; Agyemang, K.; Butterworth, M.H. (Springer, 1988)
Presents findings of a study carried out to see beef production by effective fattening system for the domestic market of Malawi with a consequent sparing of foreign exchange.